Reflecting on the Past to Shape the Future: A Systematic Review on Cross-Cultural Collaborative Learning from 2011 to 2020 - Gyasi, Juliana Fosua; Zheng, Lanqin; Long, Miaolang (Sustainability, 2021)
Cross-cultural collaborative learning in different learning domains is the road to the sustainability of economic, social, and environmental development. It creates the appropriate environment to acquire cross-cultural communication and collaboration skills for the 21st century. This study conducted a systematic review of 54 articles on cross-cultural collaborative learning published from 2011 to 2020. Based on the proposed analysis framework, the major elements of cross-cultural collaborative learning are revealed, including learners, group composition, learning environment, cross-cultural learning content, collaborative learning strategies, and research designs. The results indicated that most studies engaged learners at the university level and adopted small group sizes in cross-cultural collaborative learning activities. The online learning environment and social science learning content were widely employed in the past 10 years. Most studies adopted multiple collaborative learning strategies and lasted for 9 to 24 weeks. Most studies targeted mixed research purposes and adopted the qualitative analysis method. The findings and relevant suggestions for future studies are discussed in depth.